Bilateral differences in the trunk muscle volume of skilled golfers - Izumoto, Y.; Kurihara, T.; Suga, T.; Isaka, T. (PLOS ONE, 2018)
Repetitive mechanical load applied to a body part may lead to hypertrophy of its muscles. If a movement requires asymmetric activation of bilateral muscles, this may result in differences in muscle size between the sides. This study aimed to investigate the degree of bilateral differences in the trunk muscle volume of golfers by comparing with non-golfers. Seventeen male right-handed golfers and eleven (nine right- and two left-handed) non-golfers participated. Trunk muscle volume was determined using magnetic resonance imaging, and the degree of asymmetry was calculated as the ratio of trunk muscle volume on the left to trunk muscle volume on the right side in right-handers and vice-versa in left-handers. Golfers had significantly larger lateral abdominal wall (LA) muscle volume than non-golfers: 12.36 ± 1.12 vs. 9.96 ± 0.94 cm3/kg; erector spinae: 9.12 ± 1.16 vs. 7.88 ± 0.84 cm3/kg; psoas major (PM): 6.27 ± 0.88 vs. 5.51 ± 0.98 cm3/kg; rectus abdominis (RA): 4.15 ± 0.54 vs. 3.50 ± 0.64 cm3/kg; and multifidus: 3.61 ± 0.41 vs. 3.05 ± 0.40 cm3/kg (p < 0.05). The degree of bilateral asymmetry of the LA, PM, and RA volume was significantly greater in golfers than in non-golfers (LA: -8.63 ± 7.40% vs. 1.94 ± 2.76%; PM: -9.10 ± 5.25% vs. -0.48 ± 5.96%; RA: 6.36 ± 6.50% vs. -2.12 ± 9.64%, respectively, p < 0.05). Right-handed golfers had greater left LA and PM volume compared to the right (LA: 5.89 ± 0.55 vs. 6.48 ± 0.65 cm3/kg; PM: 3.00 ± 0.42 vs. 3.27 ± 0.47 cm3/kg; p < 0.05) and had greater right RA volume compared to the left (2.15 ± 0.32 vs. 2.00 ± 0.24 cm3/kg, p < 0.05). These findings suggest that skilled, long-term golfers develop large volume and bilateral asymmetry of their trunk muscles.